Modeling of Spray Cooling with a Moving Steel Slab during the Continuous Casting Process. Issue 4 (15th October 2018) - Ma, Haibo; Lee, Justina; Tang, Kaile; Liu, Rui; Lowry, Michael; Silaen, Armin; Zhou, Chenn Q.
Abstract : During continuous casting secondary cooling, heat is removed from slab surface through spraying water from arrays of nozzles. Efficient and uniform heat removal without causing slab cracking is desired. The present study focuses on the development and validation of a reliable numerical model which can accurately predict spray formation from flat‐fan atomizers and the heat transfer between impinging droplets and a moving hot steel slab. Water droplets are considered as the discrete phase and are tracked in a Lagrangian framework to allow detailed modeling of breakup, coalescence, and impingement. The droplet size and the heat transfer coefficient on the slab surface are validated. Both simulations show good agreements with the experimental measurements in the center of the spray, where fine droplets are generated through multiple collisions. After droplets impinge on the slab surface, a narrow low temperature region is created inside the spray coverage, and the relative motion of the spray shifts the coverage toward the upstream. Future studies are necessary in order to improve the prediction of droplet‐air interaction near the edge of the spray, where small droplets tend to coalesce and form large ones due to a lower possibility of collision. Abstract : The spray cooling during the continuous casting process is numerically analyzed through the Eulerian‐Lagrangian approach in the present study. The Linearized Instability Sheet Atomization model and the Naber and Reitz impingement model are adopted to simulate the atomization and impinging heat transfer. Both the droplet size and the heat transfer coefficient on the slab surface are validated against the experiments.